Gastric antral web presenting with esophageal stricture and severe malnutrition - Okumuş, Mustafa; Zarbaliyev, Elbrus; Gürakan, Seyitahmet; Gökçe, Selim (International Journal of Contemporary Pediatrics, 2024)
Gastric antral web is a rare cause of gastric outlet obstruction in children. Common complaints include intermittent non-bilious vomiting, bloating, pain, loss of appetite, and weight loss. Herein, we report a case of gastric antral web presenting with esophageal stricture and malnutrition, which was followed for many years with a misdiagnosis. An 8-year-old African boy was referred to our pediatric gastroenterology clinic due to recurrent vomiting and severe malnutrition. According to his medical history, the patient began experiencing non-bilious vomiting at 40 days of age and a diagnosis of gastroesophageal reflux was made. He was hospitalized multiple times and received nasogastric tube feedings in the following 4 years. He was re-evaluated for growth retardation and malnutrition at 4 years of age. He had been diagnosed with gluten enteropathy and was fed a gluten-free diet. Recently, he developed difficulty swallowing solid food and was only able to consume liquid meals. Esophagography revealed segmental stenosis in the distal portion of the esophagus. After stricture excision with thoracotomy, upper gastrointestinal series with a radiopaque substance indicated normal esophageal passage; however, prolonged gastric emptying time was also noted. Upon examination during laparotomy, a congenital web was detected in the antral region and was excised. Esophageal and gastric pathologies were consistent with stricture caused by reflux esophagitis and gastric antral web. Today, gastric antral web is mostly diagnosed and treated in infancy. Near total obstruction is relatively easy to diagnose; however, many patients with partial obstruction are followed-up for years with an incorrect diagnosis. Therefore, it should be considered in such cases, persistent vomiting and gastroesophageal reflux may be associated with esophageal stricture.